Association of Macrophage Migration Inhibitory FactorGene - 173 G/C Polymorphism with Occurrence andSeverity of Acute Pancreatitis - (:unkn) unknown (My University, 2019)
Introduction: Promoter polymorphism -173G/C of macrophage migration inhibitory factor (MIF) is related to higher MIF levels. In this study, we have investigated the effects of this polymorphism with the occurrence and severity of acute pancreatitis (AP).Methods: Sixty-two AP patients and 83 healthy volunteers were included in our study. The demographical, clinical, labora-tory and radiological findings were recorded, and peripheral blood samples were genetically analyzed.Results: In this study, 35 female and 27 male patients were included. The mean age was 51. The AP severity was mild at 37 patients, moderate at 21 and severe at four patients. Genotype and allelic distribution at patient and control groups were statistically different (p<0.001; p=0.03). Although no significant difference between mild, moderate and severe AP groups detected, there was a tendency of CC genotype and C allele frequency being higher at moderate and severe AP and GG genotype being higher at mild AP. Eight of nine SIRS developed patients had CC genotype and C allele frequency was 88.9%. The leucocyte count at CC genotype and at C allele increased.Discussion and Conclusion: According to our results, CC genotype and C allele frequency were related with AP occurrence. However, considering the severity of AP, the statistical significance could not be proven.